Simultaneous Radar-Communication Systems Using Controlled Chaos-Based Frequency Modulated Waveforms - Pappu, Chandra S.; Carroll, Thomas L.; Flores, Benjamin C. (IEEE access, 2020)
With the increase in demand for spectral resources and bandwidth constraints, efficient solutions for the coexistence of radar and communication systems are needed. Simultaneously, the development of multifunctional radio frequency (RF) systems with less hardware have received considerable attention. Most previous work on coexistence has focused on hardware design and mitigation of interference between radar and communication systems. This work proposes, a novel method for controlling a chaotic trajectory, which allows for the coexistence of both radar and communication systems. Binary information can be encoded in a chaotic state by adjusting its trajectory. In this approach, a state variable is selected to control the trajectory and generate a controlled chaos-based frequency modulated (CCBFM) waveform for joint radar-communication system signal transmission. We also design a communication receiver to decode the information and a radar receiver that extracts the signature of the target are designed accordingly. The performance of the controlled chaotic communication system is assessed in terms of the bit error ratio (BER). The analysis of the communication system shows that the CCBFM receiver performs reasonably well compared to a half-sine pulse frequency modulated (HSPFM) receiver. Analysis of the radar system performance is assessed using the entropy of the target's signature. The use of a CCBFM waveform leads to accurate target detection and classification for a signal-to-noise ratio as low as -30 dB. These analyses demonstrate that a CCBFM waveform can be successfully used for joint radar-communication systems in a shared spectrum.